Pengaruh Promosi Media Sosial Instagram dan Word Of Mouth terhadap Keputusan Pembelian Konsumen Memilih Wedding Organizer Wiwit Wedding - Jihan Apriliyani; Winna Sarikusumaningtyas (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research was conducted to test the influence of instagram social media promotions and word of mouth on purchasing decisions to choose the Wiwit Wedding wedding organizer. The data collection technique used 60 samples by distributing questionnaires and the data analysis technique was quantitative. The results of this research show that Instagram Social Media Promotion and Word of Mouth have a positive and significant effect on Consumer Purchasing Decisions when choosing Wiwit Wedding Wedding Organizers, both partially and simultaneously. The amount of 77.5% of social media promotion variables and word of mouth can influence consumer purchasing decisions to choose the wedding organizer Wiwit Wedding, while the remaining 22.5% is influenced by other variables not examined by this research.